2014
DOI: 10.1007/s12011-014-0138-x
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risks Derived from Dietary Exposure to Toxic Metals in Catalonia, Spain: Temporal Trend

Abstract: The present study was aimed at estimating the current (2012) dietary intake of arsenic (As), cadmium (Cd), mercury (Hg), and lead (Pb) by the population of Catalonia, Spain. The temporal trends with respect to previous surveys, performed in 2000, 2005, and 2008, were also determined. For that purpose, metal concentrations were analyzed in a number of widely consumed foodstuffs. A speciation study was also conducted by experimentally determining the levels of inorganic As (InAs) and methylmercury (MeHg) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
(48 reference statements)
4
28
1
Order By: Relevance
“…It should be noted that in the last few decades, due to corrective actions involving reduction of emissions of Pb in environment, this element is no longer present as before (Baldini, Novelli, & Baldini, 2004;Perell o et al, 2014): for example, a positive contribute to this trend is the reduction of Pbed-gasoline emissions from the eighties to our days (Jarup, 2003;Johnson, Siccama, Driscoll, Likens, & Moeller, 1995;Lind, Bignert, & Odsj€ o, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that in the last few decades, due to corrective actions involving reduction of emissions of Pb in environment, this element is no longer present as before (Baldini, Novelli, & Baldini, 2004;Perell o et al, 2014): for example, a positive contribute to this trend is the reduction of Pbed-gasoline emissions from the eighties to our days (Jarup, 2003;Johnson, Siccama, Driscoll, Likens, & Moeller, 1995;Lind, Bignert, & Odsj€ o, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…In 2009, however, the European Food Safety Authority (EFSA) [31,32] reevaluated data on dietary cadmium intake and set a new PTWI of 2.5 μg/kg b.w. (0.357 μg/kg b.w./day) [33]. Approximately 66% of the sample exceeded the threshold for this element.…”
Section: Discussionmentioning
confidence: 99%
“…was not appropriate because no evidence of a critical threshold for lead-induced effects exists. In 2011, the JECFA concluded that because of prior analyses, a critical threshold would be considered health protective [33]. Nevertheless, all of the women had values well below the PTWI.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of seafood in Spain is notorious, contributing to the intake of up to 27% of protein and 14% of polyunsaturated fatty acids among adults (AECOSAN, 2012). Similarly to other environmental contaminants, such as persistent organic pollutants or heavy metals (Domingo et al, 2012a,b;Perelló et al, 2014), diet could be the most important route of exposure to musks. Unfortunately, there is a complete lack of knowledge regarding the dietary intake of musks, in front of other potential exposure pathways.…”
Section: Introductionmentioning
confidence: 99%